PERAN TEKNOLOGI PENGOLAHAN PANGAN PADA GIZI DAN KESEHATAN MAYARAKAT (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Food is a basic human need. Throughout the history of human civilization, humans have been able to meet their food needs to sustain their lives. Using their intellectual and creative powers, humans have created numerous techniques and technologies to produce, store, preserve and consume food. Some of these technologies later developed into food technology as is known today. The application of food technology for food processing (producing processed food) has supported human civilization, by ensuring the availability of safe, nutritious, quality, affordable, functional food, in accordance with social, economic, cultural, religious and belief requirements. A diet consisting of a combination of fresh and processed foods, has become an important part of food culture to maintain and improve the quality of human life. Processed food contributes to food security (ensuring the availability of sufficient safe food) and nutritional security (ensuring the availability of nutritional sources to meet public health requirements). This paper argues that the “role of food processing technology in nutrition and public health” includes ensuring safety, maintaining, and improving nutritional quality, increasing palatability and sensory quality, adding nutrients (fortification, enrichment, etc.), extending shelf life (ensuring safety, inhibiting spoilage). and quality degradation), provide practicality (convenience), provide choice, facilitate transportation (ensure better distribution), reduce food loss and food waste, and ensure affordability.